Changes in group behaviour in response to a preferred environment reflect positive affect - Tanja K. Kleinhappel; Thomas W. Pike; Oliver H. P. Burman (Scientific Reports, 2023)
Abstract When observed in their preferred environments, animals display behavioural changes, such as an increase in resting or a reduction in agonism, suggestive of positive affect and improved welfare. However, most studies focus on the behaviour of individuals or, at most, pairs of animals; even though in group-living animals beneficial environmental changes may impact on how the group behaves as a whole. In this study, we investigated whether experiencing a preferred visual environment affected the shoaling behaviour of zebrafish (Danio rerio) groups. We first confirmed a group preference for an image of gravel placed underneath the base of a tank compared to a plain white image. Second, we observed replicated groups either with or without the preferred (gravel) image present to determine if a visually enriched and preferred environment could elicit changes in shoaling behaviour. We found a significant interaction between the observation time and test condition, with differences in shoaling behaviour reflective of increased relaxation emerging gradually over time in the gravel condition. The findings of this study reveal that experiencing a preferred environment can alter group behaviour, making such holistic changes valuable as potential indicators of positive welfare.